Professionalism experiences of undergraduate learner nurses during their 4-year training programme at a Higher Education Institution in the Western Cape, South Africa - Bimray, Portia (Curationis, 2019)
BACKGROUND: Professional socialisation of student nurses needs to be integrated into the formal teaching and learning during the nursing programme. Embedded in the training programme are professional values that are used synonymously with nursing professionalism. Professionalism is the conduct, qualities, values, vision, mission and/or goals that characterise a profession, and describes behaviours that are expected within the profession’s members. However, one’s values are shaped by one’s experiences, influence one’s behaviour and interactions with others, and are manifested in many aspects of professional behaviour. New nurses to the profession are expected to display behaviours of professionalism, thus requiring nurse training schools to help students internalise these behaviours. Nurse educators therefore carry a responsibility to shape future nurses’ growth towards professionalism. OBJECTIVES: This article reports on the experiences of undergraduate student nurses regarding nursing professionalism during their 4-year training programme at a Higher Education Institution in the Western Cape, South Africa. METHOD: A qualitative, exploratory and descriptive design was applied. Eight focus group discussions were conducted with first- to fourth-year student nurses registered for the undergraduate nursing programme. Data were transcribed verbatim and analysed using open coding. Ethical principles and trustworthiness were maintained throughout the study. RESULTS: Six main themes indicated that undergraduate student nurses experienced issues with role modelling, language barriers, their own understanding of professional behaviour, reasons for students and practitioners’ unprofessional behaviour, prejudice towards degree students and students’ professional or unprofessional behaviour experienced as contributing to the image of the profession. CONCLUSION: Student nurses received mixed messages leading to emotional turbulence. They needed clear guidance from role models to demonstrate how to behave professionally.